Una especie nueva de Tectaria (Filicales: Tectariaceae) en Panamá - Rojas Alvarado, Alexander Francisco (Lankesteriana: International Journal on Orchidology, 2006)
Tectaria dressleri A. Rojas, presently known only from Panama, is described as a new species characterized by entire fronds, pilose blade and glabrous indusium.